Statement on the active substance acetamiprid. (24th January 2022) - ,; Hernandez Jerez, Antonio; Adriaanse, Paulien; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Focks, Andreas; Marinovich, Marina; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; Tiktak, Aaldrik; et al.
Abstract: Acetamiprid is a pesticide active substance with insecticidal action currently under the third renewal (AIR3) of the Commission implementing regulation (EU) No 844/2012. Following concerns that this substance may pose high risks to humans and the environment, the French authorities asked the Commission to restrict its uses under Article 69 of Regulation (EC) No 1107/2009. To support this request, competent Authorities from France cited a series of literature papers investigating its hazards and/or exposure to humans and the environment. Consequently, the EFSA PPR Panel was mandated to advise on the likelihood that body of evidence would constitute proof of serious risks to humans or the environment. Therefore, the EFSA PPR Panel evaluated the likelihood of these studies indicating new or higher hazards and exposure to humans and the environment compared to previous EU assessments.A stepwise methodology was designed, including: (i) the initial screening; (ii) the data extraction and critical appraisal based on the principles of OHAT/NTP; (iii) the weight of evidence, including consideration of the previous EU assessments; (iv) the uncertainty analysis, followed, whenever relevant, by an expert knowledge elicitation process. For human health, no conclusive evidence of higher hazards compared to previous assessment was found for genotoxicity, developmental toxicity, neurotoxicity including developmental neurotoxicity and immunotoxicity. However, due to the lack of adequate assessment of the current data set, the PPR Panel recommends conducting an assessment of endocrine disrupting properties for acetamiprid in line with EFSA/ECHA guidance document for the identification of endocrine disruptors. For environment, no conclusive, robust evidence of higher hazards compared to the previous assessment was found for birds, aquatic organisms, bees and soil organisms. However, the potential of high inter‐species sensitivity of birds and bees towards acetamiprid requires further consideration. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2022.7030/full